Automated Text Translation - Khuzyatov, Shafik Shaekhovich; Galiullin, Lenar Ajratovich (International Journal of Criminology and Sociology, 2022)
The paper analyzed the problem of accessibility of content in other languages, it was found that many content may not be translated into the native language of users who want to access it, but at the same time there are many who want to help other users with this problem. The solution is a special information system that allows you to easily register and create your own translation, in which other users can participate, or join another already created one and help. As a result, the interested user can easily download the translation result and use it at his own discretion. The analysis of business processes for the creation and translation of the text was carried out. Based on this analysis, requirements for a future solution were developed. Business requirements were also identified. Among other things, a system use case model was developed and use case specifications were described. Lists with functional and non-functional requirements have also been developed. The functional model of the system was shown - algorithms: authorization, registration, password recovery, creating a new translation, generating a file with a new translation, generating a list of translations, managing users, viewing a translation, editing a translation text, checking the correctness of a translation, and moderating translations. A class diagram was developed, where you can see the main entities of the system and their relationships. A sequence diagram was also developed. The architecture of the information system was described. The system was implemented using the React.JS library and the Spring framework. The main processes of the system users were also described.